HEALTH Attributes for Budding Health Care Professionals: A Need to Revisit Existing Curricula - Dubhashi, Prof. Dr. Siddharth P. (International Journal of Innovative Research in Medical Science, 2025)
The paper highlights the importance of Graduate Attributes of an Institution. HEALTH Attributes for health sciences include: H: Holistic approach with cultural competence; E: Empathy for fellow beings and patients; A: Academic Leadership; L: Effective Liasoning with proficient communication skills; T: Team-building and collaboration; H: Harness creativity and innovation with critical thinking. Institution should foster critical thinking among the budding professionals by way of evidence-based learning strategies. There is a dire need to formally adopt Peer-Assisted Learning in the curriculum. Delegative leadership style should be utilized for small group teaching-learning activities, including field visits. Curriculum Mapping should be a mandatory integral component in tune with stated graduate attributes. Every health science graduate should possess all-round qualities, making him / her, a “competent basic health care professional”. It would really be worthwhile to have uniformity in graduate attributes for health sciences, thereby having a structured strategy for evaluation of program outcomes.